Robert Hoyland’s Epigraphic Approach and Its Implication For The Historical Study Of The Qur’an - Sofiyul, Achmad; Rochmaniyah, Inayah; Touré, Youcha Alassane (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study examines epigraphy as an innovative and empirically grounded approach to understanding the Qur'an. It aims to analyze Robert Hoyland’s epigraphic discourse in Qur'anic studies, critically assess the factors underlying the emergence of the epigraphic approach, and explore its theoretical implications for contemporary Islamic scholarship. Employing a qualitative research design, this study adopts Van Dijk’s Critical Discourse Analysis as its theoretical framework, as it enables the examination of ideological, historical, and contextual dimensions embedded within epigraphic discourse. This framework is essential for understanding how epigraphy shapes interpretive authority and reconfigures methodological assumptions in Qur'anic studies. The findings demonstrate that the epigraphic approach offers an empirical basis for understanding the Qur'an through inscriptions, manuscripts, and material evidence from the formative period of Islam. This approach is methodologically significant for its capacity to illuminate the historical context of Qur'anic revelation, substantiate the stability of the Qur'anic text, and reveal its dynamic interaction with pre-Islamic cultural and religious traditions. Moreover, the study shows that epigraphy contributes to a transformation of hermeneutical methodology by shifting Qur'anic interpretation toward a historically informed and materially anchored perspective. Theoretically, this research broadens the epistemological horizon of Qur'anic interpretation and underscores the urgency of a multidisciplinary approach in contemporary Qur'anic studies. By situating epigraphy within critical discourse analysis, the study affirms its relevance not merely as an auxiliary tool, but as a significant paradigm in rethinking the foundations of Qur'anic scholarship. Contribution: This research contributes to contemporary Qur'anic studies by critically articulating the epigraphic approach as an alternative epistemological and methodological framework for examining and understanding the Qur'an.